2017
DOI: 10.1186/s12245-017-0143-x
|View full text |Cite
|
Sign up to set email alerts
|

Markers of diuretic resistance in emergency department patients with acute heart failure

Abstract: BackgroundLoop diuretics are common therapy for emergency department (ED) patients with acute heart failure (AHF). Diuretic resistance (DR) is a term used to describe blunted natriuretic response to loop diuretics. It would be important to detect DR prior to it becoming clinically apparent, so early interventions can be initiated. However, several definitions have been proposed, and it is not clear if they identify similar patients. We compared these definitions and described the clinical characteristics of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 19 publications
(31 reference statements)
3
28
0
1
Order By: Relevance
“…Stage D dogs made up 21% of the CHF population in our study. This percentage is similar to reports of people with CHF that show diuretic resistance, but we do not know if all (or any) of these dogs had diuretic resistance . Laboratory variables, including FE Na, uNa, uNa:uK, and uNa:Fur, have been proposed as markers of diuretic resistance, associated with refractory CHF, in people.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Stage D dogs made up 21% of the CHF population in our study. This percentage is similar to reports of people with CHF that show diuretic resistance, but we do not know if all (or any) of these dogs had diuretic resistance . Laboratory variables, including FE Na, uNa, uNa:uK, and uNa:Fur, have been proposed as markers of diuretic resistance, associated with refractory CHF, in people.…”
Section: Discussionsupporting
confidence: 75%
“…Diuretic resistance is identified in up to 17% of people with CHF and also is suspected to occur in dogs . Although reports of diuretic resistance are lacking in veterinary medicine, the American College of Veterinary Internal Medicine (ACVIM) considers a role for diuretic failure in the description of refractory heart disease (HD), termed Stage D .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Evaluating natriuresis and diuresis within 1 h of diuretic administration could identify patients within 2-3 h of ED presentation who may need early treatment intensification. In contrast to prior studies that were conducted in the inpatient setting after admission and initial therapy, we followed up patients in the ED and documented urine output in the first 6 h as a measure of acute diuretic response.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study also suggested a relationship between urinary sodium and hospital LOS. 15 Evaluating natriuresis and diuresis within 1 h of diuretic administration could identify patients within 2-3 h of ED presentation who may need early treatment intensification. Other markers of response to diuretic therapy, such as weight loss and fluid excretion, have been used and have been inconsistent markers of decongestion and treatment endpoints.…”
Section: Discussionmentioning
confidence: 99%